Adam Dubin, Dean Vuletic and Antonio Obregón (Eds.). The Eurovision Song Contest as a Cultural Phenomenon. From Concert Halls to the Halls of Academia. Published by Routledge, New York (2023), 275 pp. (Communication & Society, 2024)
Book Review